Adolescent Idiopathic Scoliosis Bracing Success Is Influenced by Time in Brace: Comparative Effectiveness Analysis of BrAIST and ISICO Cohorts. Issue 17 (1st September 2020) - Dolan, Lori A.; Donzelli, Sabrina; Zaina, Fabio; Weinstein, Stuart L.; Negrini, Stefano
Abstract : Study Design: Comparative effectiveness study Objective: To evaluate factors leading to higher percentage of brace failures in a cohort of North American patients with adolescent idiopathic scoliosis relative to their peers in Italy. Summary of Background Data: Studies of bracing in United States have shown worse outcomes than studies from European centers, possibly due to sample characteristics or treatment approaches. Methods: Sample: Braced patients, aged 10 to 15, Risser <3, Cobb 20°- to 40°, observed to Cobb ≥40° and/or ≥Risser 4 selected from prospective databases. Comparators: Bracing per Bracing in Adolescent Idiopathic Scoliosis Trial (BrAIST) (TLSO) and Italian Scientific Spine Institute (ISICO) protocol (SPoRT braces with or without SEAS exercises). Baseline characteristics (sex, age, BMI, Risser, Cobb, curve type) and average hours of brace wear/day. Differences in programs ( e.g., SEAS, type of brace, weaning protocol) were captured by a variable named "SITE." Outcome : Treatment failure (Cobb ≥40 before Risser 4). Statistics: Comparison of baseline characteristics, analyses of risk factors, treatment components, and outcomes within and between cohorts using logistic regression. Results: A total of 157 BrAIST and 81 ISICO subjects were included. Cohorts were similar at baseline but differed significantly in terms of average hours of brace wear: 18.31 in the ISICO versus 11.76 in the BrAIST cohort. Twelve percent of the ISICO and 39% of the BrAIST cohort had failed treatment. Age, Risser, Cobb, and a thoracic apex predicted failure in both groups. SITE was related to failure (odds ratio [OR] = 0.19), indicating lower odds of failure with ISICO versus BrAIST approach. With both SITE and wear time in the model, SITE loose significance. In the final model, the adjusted odds of failure were higher in boys (OR = 3.34), and those with lowest BMI (OR = 9.83); the odds increased with the Cobb angle (OR = 1.23), and decreased with age (OR = 0.41) and hours of wear (OR = 0.86). Conclusion: Treatment at the ISICO resulted in a lower failure rate, primarily explained by longer average hours of brace wear. Level of Evidence: 3 Abstract : The aim of this study is to evaluate potential factors leading to higher percentage of brace failures in a cohort of North American adolescent with idiopathic scoliosis relative to their Italian peers. Our findings suggest that the Italian better outcomes may be explained by longer average hours of brace wear.